Effect of mouthwash with Boswellia extract on the prevention of dental plaque formation in patients under mechanical ventilation - Marziye Ziaie Rad; Hossein Taherian (Kashan University of Medical Sciences, 2020)
Background: Oral hygiene is a crucial nursing care in the intensive care unit (ICU) that can prevent ventilator-associated pneumonia. Objectives: This study compares the effect of mouthwash with Boswellia extract and chlorhexidine on the prevention of dental plaque formation in ICU patients having an endotracheal tube. Methods: A clinical trial was performed on 90 patients under mechanical ventilation in the ICU of Ayatollah Kashani Hospital in Isfahan, Iran, in 2018. The study data were collected using a demographic information form, a checklist, and the O'Leary dental plaque index (ODPI). The patients were randomly divided into two groups to receive mouthwash using solutions containing Boswellia or chlorhexidine. Data were analyzed using the Kolmogorov-Smirnov test, analysis of variance, independent samples, and paired t-tests. Results: Most of the patients were male (76.67%), with a smoking background (60%) and in the age range of 18-38 years. The two groups did not significantly differ in terms of demographic characteristics (P > 0.05). The mean ODPI was 0.89 ± 0.07 at baseline in the Boswellia group and changed to 0.67 ± 0.05 after the intervention (P < 0.001). Furthermore, the mean ODPI was 0.93 ± 0.03 in the chlorhexidine group and change to 0.77 ± 0.09 after the intervention (P < 0.001). Conclusions: Both Boswellia and chlorhexidine mouthwashes were effective in the prevention of dental plaque in patients under mechanical ventilation.